Operations and planning of integrated renewable energy system: a survey - Babatunde, O.M.; Munda, J.L.; Hamam, Y. (International Conference on Renewable Energies for Developing Countries (Online), 2020)
Hybrid renewable energy system (HRES) also known as integrated renewable energy system is fast gaining vast research attentions worldwide. This is due to its efficacy in remote and rural electrification. Hence, HRES sizing and design has been formulated and presented by numerous studies based on various viewpoints (formulation, optimization methods, configuration, coupling methods etc.). This paper presents a brief survey of various existing and emerging themes with respect to HRES planning and operations. A discussion on the challenges and future research directions on the subject of HRES are also presented.